Using Interactive Web-Based Learning Multimedia to Assess Competency Standards for Installing LAN Among Vocational High School Students in Padang, Indonesia - Suryani, Karmila; ., Khairudin; Widyastuti, Rini; Amelia, Riska (International Journal of Engineering and Technology, 2018)
This research is aimed at creating an interactive, valid, practical and effective WebÂ¬Â¬Â¬-Based Learning Multimedia for assisting the students to learn the school subject: Installation of Local Area Network (LAN), and to meet the competency standard in such subject. To create the learning multimedia the researchers adopted Cooperâ€™s Stage-Gate Method by applying product development phases, namely: Vision, Conception, Design, Prototype, and Production. After the design process had been completed, the multimedia was validated by a team of multimedia experts, and reached a score of 94.96% which is categorized as Highly Valid. For practicality analysis, the Researcher distributed questionnaires to relevant parties so as to know the level of students interest, the process of using, the increase of active learners, the sufficiency of time, and for evaluation purposes, and it resulted in a score of 87% which is categorized as Practical. Such validity and practicality analysis were done at the Phase of Prototype. Finally, the Researchers shared the Application to all students of Computer and Network Engineering Department in Padang, Indonesia, and the results were fairly encouraging in which the learning outcomes of the students can reach the figure of 87%, and the grades achieved by the students were Above Minimum Passing Criteria. In view of such results, it can be concluded that this learning multimedia has met the requirement for a mass application. Â Â